Co3O4 nanocrystals/3D nitrogen-doped graphene aerogel: A synergistic hybrid for peroxymonosulfate activation toward the degradation of organic pollutants. (November 2018) - Yuan, Ruixia; Hu, Lin; Yu, Peng; Wang, Zhaohui; Wang, Huaiyuan; Fang, Jingyun
Abstract: 3D porous Co3 O4 /nitrogen-doped graphene aerogel (NGA) hybrid for heterogeneous activation of peroxymonosulfate (PMS) was prepared by feasible hydrothermal and freeze-drying methods. The morphology, crystal structure and chemical composition of the catalyst were investigated by scanning electron microscopy, X-ray diffractometer, X-ray photoelectron spectroscopy, Raman spectra and Fourier transform infrared spectroscopy. Co3 O4 /NGA at a high N doping level of 7.6% (in atomic percentage) exhibited excellent catalytic performance for acid orange 7 (AO7) degradation, with almost complete removal within 30 min. Moderate PMS content, higher temperature and lower solution pH conditions would facilitate the decomposition of AO7. The catalyst possesses excellent long-term stability and recycling performance with simple separation and post-treatment approaches. Kinetic model was developed to simulate the transformation of main active radical species and the AO7 oxidation profiles, considering effects of coexisting ions (Cl − and HCO3 − ). Based on results of electron spin resonance, typical quenching tests and kinetic calculation, sulfate radicals play dominate role in AO7 degradation. Co3 O4 nanocrystals and the new active sites created by nitrogen doping into graphene honeycomb network should synergistically contribute to the high degradation efficiency. This work has expanded the possibility of recyclable catalysts design for heterogeneous activation of PMS, with a dual catalytically active center and desirable stability. Graphical abstract: Image 1 Highlights: Co3 O4 nanocrystals were supported on 3D monolith N-doped graphene aerogel (NGA). Co3 O4 /NGA possesses excellent long-term stability and recycling performance. Kinetic modeling was developed to simulate transformation of main active radicals. Macroscopic Co3 O4 /NGA can be easily separated and reused with low cobalt leaching.